2009
DOI: 10.1016/j.ijantimicag.2009.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized silver–anionic clay matrix as nanostructured ensembles with antimicrobial activity

Abstract: Nanostructured ensembles of silver nanoparticles/zinc-substituted anionic clay matrix (Ag/ZnLDH) were obtained by a simple synthetic route in which reconstruction of the layered clay, synthesis of the silver nanoparticles and their organisation on the clay surface took place in a single step at room temperature. The morphology, composition and phase structure of the prepared powders were characterised by X-ray diffraction, infrared spectroscopy, transmission electron microscopy, X-ray photoelectron spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…TiO 2 , exceeding the Schottky barrier, has been reported [17][18][19][20] A c c e p t e d M a n u s c r i p t 7 introduced into the aqueous solutions of silver or gold salts [21,22]. In this work, assemblies procedure from metal nitrates, Na 2 CO 3 , and NaOH in aqueous solutions controlled at pH 8 [10].…”
Section: Introductionmentioning
confidence: 92%
“…TiO 2 , exceeding the Schottky barrier, has been reported [17][18][19][20] A c c e p t e d M a n u s c r i p t 7 introduced into the aqueous solutions of silver or gold salts [21,22]. In this work, assemblies procedure from metal nitrates, Na 2 CO 3 , and NaOH in aqueous solutions controlled at pH 8 [10].…”
Section: Introductionmentioning
confidence: 92%
“…147 They evaluated the antimicrobial effect of AgNPs alone and hybrid AgNP LDHs with respect to time, and found that AgNP LDHs retained the inhibition zone against the Gram-positive S. aureus (American Type Culture Collection [ATCC] 25923) and the Gram-negative E. coli (ATCC 35218). However, the AgNP zone of inhibition was found to almost disappear with time.…”
Section: Biogenic Silver Nanoparticle-fabricated Layered Double Hydromentioning
confidence: 99%
“…However, the AgNP zone of inhibition was found to almost disappear with time. 147 Titanium-based layered double hydroxides with antimicrobial properties Zhao et al designed nanoscale material with photocatalytic activity. 141 They developed Zn-Ti LDH nanosheets in the size range of 40-80 nm with a band gap of about 2.3 eV.…”
Section: Biogenic Silver Nanoparticle-fabricated Layered Double Hydromentioning
confidence: 99%
“…The hydrotalcite-lik e clay and zinc substituted hydrotalcite-lik e clay, denoted as MgLDH and ZnLDH were obtained by the coprecipitation method following the procedure described elsewhere [13,17]. After calcinatio n at 750 °C, for 8 h, these samples were denoted as MgLDH750 and ZnLDH750, respectively.…”
Section: Catalysts Synthesismentioning
confidence: 99%